2014
DOI: 10.1093/ejcts/ezu028
|View full text |Cite
|
Sign up to set email alerts
|

Revised ESTS guidelines for preoperative mediastinal lymph node staging for non-small-cell lung cancer

Abstract: Accurate preoperative staging and restaging of mediastinal lymph nodes in patients with potentially resectable non-small-cell lung cancer (NSCLC) is of paramount importance. In 2007, the European Society of Thoracic Surgeons (ESTS) published an algorithm on preoperative mediastinal staging integrating imaging, endoscopic and surgical techniques. In 2009, the International Association for the Study of Lung Cancer (IASLC) introduced a new lymph node map. Some changes in this map have an important impact on media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
599
0
28

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 678 publications
(670 citation statements)
references
References 64 publications
8
599
0
28
Order By: Relevance
“…The 2014 guidelines of the European Society of Thoracic Surgeons indicate endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) as the initial approach for pathological evaluation of mediastinal lymph nodes (1,2). In the last 15 years EBUS-TBNA has increasingly been used for minimally invasive diagnosis of mediastinal-hilar lymph node metastases in patients with NSCLC, and in selected cases this technique has replaced mediastinoscopy, videothoracoscopy and traditional transbronchial biopsy (2).…”
Section: Introductionmentioning
confidence: 99%
“…The 2014 guidelines of the European Society of Thoracic Surgeons indicate endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) as the initial approach for pathological evaluation of mediastinal lymph nodes (1,2). In the last 15 years EBUS-TBNA has increasingly been used for minimally invasive diagnosis of mediastinal-hilar lymph node metastases in patients with NSCLC, and in selected cases this technique has replaced mediastinoscopy, videothoracoscopy and traditional transbronchial biopsy (2).…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent study showed that EBUS-TBNA was more sensitive (88% vs. 91%) and more accurate (92% vs. 89%) when compared to mediastinoscopy for evaluating lymph node stations 2R, 2L, 4R, 4L, and 7 (30). The European Society of Thoracic Surgeons have thus changed their guidelines to recommend EBUS-TBNA as first line method of mediastinal lymph node assessment in patients with nonsmall cell lung cancers greater than 3 cm, located centrally within the lung, or with suspected N2 disease based on preprocedure imaging (31).…”
Section: Ebusmentioning
confidence: 99%
“…Therefore, several minimally invasive methods have been used for tissue sampling including conventional bronchoscopy with TBNA guided by fluoroscopy or EBUS RP, but the yield varied widely (38)(39)(40). After one large randomized control trial compared surgical staging or combined EBUS-TBNA and transesophageal ultrasound fine needle aspiration (EUS-FNA) followed by surgical staging (41), EBUS CP guided TBNA (EBUS-TBNA) is now the first choice for mediastinal LN staging (9,42). Another single arm study also supports that EBUS TBNA is better than mediastinoscopy (43).…”
Section: Ebus Cpmentioning
confidence: 99%